Turning your computer into a road manager. - Jeter, Dennis (Downbeat, 1996)
Discusses Wynton Marsalis Enterprises' use of database software and computers to manage their musicians' performance schedules. Utilization of computer databases to record fans' names; Inventory of equipment; Communication of tours details; Preferred software and hardware.